Local Social Capital: Revisiting the Measurement and Establishing Manageable Indicators - Seo, Inseok; Lee, Youhyun; Song, Minsun (Lex Localis, 2024)
The social links between community entities are frequently regarded as a valuable asset for local economic development. Opinions diverge regarding the particulars of social capital and its constitution within social relations, despite its fundamental nature coming from these connections. Diverse public and private activities, according to Putnam (1995b), could constitute local social capital. While social capital can be conceptualized as private relations, assessing and debating it from the standpoint of local governments presents a formidable challenge. The distinction between the public and private spheres regarding the character of human activities was advanced by Arendt (1958). This study aims to frame the possible indicators for measuring local social capital by adopting Arendt’s classical theory. By applying it to the social capital of the social communities, the research fills a gap in the discussion between public and private spheres. The integrated framework theoretically provides a backbone for the distinguished perspectives of social capital in different levels of human activities. As well as categorizing manageable and non-manageable indicators, it also provides practical policy implications for the criteria local governments place an emphasis on for managing the level of social capital in a region. It is anticipated that the framework will advance the expansion of the theoretical literature on social capital by identifying measures at two distinct levels: individual and collective characteristics.
Keywords: local governments; manageable indicators; public activities; social capital; social relationships